SCREENING OF VOLATILE COMPOUNDS IN SHRIMP PASTE AS CANDIDATES FOR ALZHEIMER’S DRUGS THROUGH BIOINFORMATIC ANALYSIS - Isdaryanti Isdar; Alexander Kurniawan Sariyanto Putera; Indriani Susi (BIOMA: Jurnal Biologi dan Pembelajarannya, 2023)
Alzheimer's Disease (AD) currently has no definitive medication. The trend has shifted towards utilizing bioactive compounds found in fermented foods as potential medications for AD. Several studies have identified AD medication and prevention compounds in certain types of fermented foods. However, the potential of shrimp paste, a popular Indonesian food rich in bioactive compounds, in preventing and curing AD has not been studied yet. Therefore, this research aims to identify potential volatile compounds in shrimp paste that could be candidates for AD medication. The first method involves a systematic review to collect volatile compound data from Indonesian shrimp paste. Subsequently, an in silico approach is used to screen potential compounds through three steps: analyzing biological activity, predicting target proteins, and analyzing toxicity. The results reveal 68 volatile compounds, 9 potential compounds, and only 6 compounds with a probability value greater than 0.3. These compounds are then tested in silico for correlation with AD based on the way2drug website. The analysis identifies 30 potential target proteins for AD medication. However, the pirazina compound is found to have carcinogenic activity, highlighting the need for further in vitro and in vivo analyses to identify potentially volatile compounds that could be candidates for AD medication.